A pesca artesanal da frota de Mosqueiro (Belém - Pará) e o uso do ambiente pela dourada (Brachyplatystoma rousseauxii-Castelnau, 1855) - OLIVEIRA, Diogo Marques (2007)
Considering the artisanal landing sites in the Amazon estuary, Mosqueiro Island, located in the south of the Bay of Marajó, is commercially very important and, as in nearby loading terminal (Miramar), the imminence of an environmental disaster is real. However, there is no detailed information on the fishery and the use of commercially important species, as Gilded catfish (Brachyplatystoma rousseauxii) in the region. With the objective of describing the fishing activity and the use of the region by the Gilded catfish, landings were monitored in Cajueiros Bridge (Mosqueiro) from December 2005 to November 2006. Moreover, the fishery boats were recorded using specialized log-books and trained personnel from the community. The index of relative abundance CPUE (kg/trip) was used to identify the most important species and their catch period, seasonality of the fleet, fishing sites and gross revenue. Considering the Gilded catfish, 30 individuals were obtained from commercial fishery in Mosqueiro from December 2005 to August 2006 in a bimensal basis. Individuals were weighted, measured and gonads were collected with the objective of evaluating the use of the region for reproduction. It was registered 128 fishing boats and Barcos de pequeno porte dominated followed by Canoas motorizadas. Technological differences between boats categories were observed, except in relation to boat length, mean monthly production and storage capacity. Barcos de médio porte present a greater crew and fishing days but they carry out less trips by month in relation to the others categories. Gill nets are mostly used in the area, and the mesh most frequently employed are 50, 60 e 70 mm (streched mesh size). Barcos de médio porte have larger nets when compared to others categories. The main species captured in the region are Silver croaker (Plagioscion squamosissimus), Pacora (Plagioscion surinamensis), Gilded catfish (Brachyplatystoma rousseauxii) and Yellowfin river pellona (Pellona spp.). Fleet from Cajueiros bridge fish mainly in fishing sites near the island during the catch period of the main species (May to December) moving to Marudá region during the offpeak season (January to April) following, mainly, the schools of Gilded catfish. Periods of maximum abundance was the first and the forth trimester for Canoas motorizadas and Barcos de pequeno porte respectively. The fishing sites Ponta Fina and Areia do Cotijuba showed the largest annual relative abundance with the main catch of Gilded catfish and Pacora, respectively. Gilded catfish was regular during the whole period with highest abundance in Ponta Fina and December. Pacora highest abundance was recorded in Marudá (98 kg/trip) and September. Yellowfin river pellona occurred mainly in Enseada and in June. In Mosqueiros Island, fish annual production was estimated in approximately 1.000 tons, leading to a gross revenue of R$ 3 million. Barcos de pequeno porte contributed to 42% of the total production and with 61% of the gross revenue. Silver croaker contributed to 26% of total production and Gilded catfish with 35% of the gross revenue. This species was considered the most valuable fish resource in the area. Sampled individuals measured from 27 to 100 cm total length, and individuals of 50 to 60 cm dominated. Sexual proportion favored females (1:2,2 male:female) which were most numerous for most length classes and months, except February. For this species, the area is not used for breeding but for nursery and feeding purposes. In the situation of an environmental disaster a waste of approximately 1.000 tons and R$ 3 millions for the fishery industry in Mosqueiros Island can be reported. Moreover, an accident in the area could also affect the young population of Gilded catfish causing harmful effects in a long term for catch and economy of the area.